Pola Asuh Orang Tua Pada Remaja Yang Melakukan Kenakalan Di Sekolah Menengah Pertama - Maemunah, Ai; Yusuf, Hediyana; Setyo Dwi Andhini, Citra (Jurnal Kesehatan Mahardika, 2024)
Juvenile delinquency is an act or behavior that is contrary to the law and social norms carried out by adolescents. One of the causes of juvenile delinquency is the inappropriate parenting pattern applied to adolescents, thus forming a negative character of adolescents. This study aims to identify how the parenting pattern of adolescents who commit delinquency in junior high school. This type of research is quantitative descriptive with respondents being students who have a history of committing delinquency in junior high school totaling 36 students. Parenting patterns were measured using the Style of Parenting questionnaire with the components seen being warmth and control. The results of this study explain that 44.4% of parenting patterns are permissive indulgent, 33.3% authoritarian, 13.9% democratic and 8.3% permissive neglectful. The conclusion of this study is that the parenting pattern of parents with students who experience delinquency is permissive indulgent and neglectful.